Analisis Berpikir Komputasi Siswa Dalam Menyelesaikan Permasalahan Matematika: Studi Literatur Review - Mayang Nabila; Yahfizham Yahfizham (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
Computational thinking is a way of thinking that students must have. Currently, many students do not yet know how computing can be applied in mathematics learning. For this reason, this research focuses on analyzing students' computational thinking in solving mathematical problems. This research takes the type of literature study research by identifying and evaluating the results of previous research. Data analysis was carried out using an interactive model which uses 4 steps in the analysis stages, namely: 1) Data collection, 2) Data condensation, 3) Data presentation and 4) Data verification. This research identified 3 previous articles. From the results of this research, it is found that computational thinking in solving mathematical problems can still be said to be not very good..